Galyean Appreciation Club Review: revisiting nutrition and health of newly received cattle—what have we learned in the last 15 years?. (5th March 2022) - Galyean, Michael L; Duff, Glenn C; Rivera, J Daniel
Abstract: Our objective was to review the literature related to the health and management of newly received cattle published since a previous review by Duff and Galyean (2007) . Bovine respiratory disease (BRD ) continues to be a major challenge for the beef industry. Depending on disease severity, animals treated for BRD have decreased performance and lowered carcass value. Diagnosis of BRD is less effective than desired, and progress on developing real-time, chute-side methods to diagnose BRD has been limited. Systems that combine lung auscultation with temperature and body weight data show promise. Assessment of blood metabolites and behavior monitoring offer potential for early identification of morbid animals. Vaccination and metaphylaxis continue to be important tools for the prevention and control of BRD, but antimicrobial resistance is a concern with antibiotic use. Dietary energy concentration and roughage source and level continue to be important topics. Mineral supplementation has received considerable attention, particularly the use of organic vs. inorganic sources and injectable minerals or drenches given on arrival. The use of probiotics and prebiotics for newly received cattle has shown variable results, but further research is warranted. The health and nutrition of newly received cattle will continue to be an important research area in the years to come. Lay Summary: Bovine respiratory disease (BRD ) is a significant economic and animal welfare challenge for the beef industry. Experiments related to the health and management of newly received cattle published in the last 15 yr were reviewed. Limited progress is being made in developing accurate, real-time methods for diagnosis of BRD, and overall, diagnosis is less effective than desired. Measurement of lung and heart sounds combined with rectal temperature have been studied as diagnostic tools, as well as measurement of blood metabolites and remote monitoring of behavior. Vaccination for viral and bacterial BRD agents and mass treatment of cattle with antibiotics continue to be important tools for prevention and control of BRD, but the development of antimicrobial resistance is a concern. Energy and roughage concentration as well as roughage source continue to be important dietary considerations, as does mineral supplementation, with mineral source and injectable minerals receiving significant research attention. Probiotics and prebiotics fed to newly received cattle have shown variable results in terms of effects on the incidence of BRD and animal performance. Additional research is needed to define optimal diagnostic, management, and nutritional practices for newly received cattle. Abstract : Management and nutritional research conducted over the past 15 yr related to the health and nutrition of newly received beef cattle is reviewed.